(untitled) (Al-Mansour Journal, 2023)
Previously, and up to now the fingerprint was used in identification the persons, but with the development of the sciences and complications of the life it was necessary to refer to other parts of the human body such as the parts of the eyes which is under our considerations. There are many methods used to distinguish persons from each other using fingerprints, via vibration of sound waves, through the shape of the ear, the color of the eyes and the iris. But in this research the geometrical relationship between the eyes for each person in which differs from one to another was found. Also, it can be find more than a geometrical relationship between the eyes in order to have more than geometrical properties and the relation between them and take these relationships as database information in order to compare with other wanted properties. In this paper, a DB technique was used which contains all eyes geometrical parameters. Practically, a good results more than 85% was found.